Long-stored soil carbon released by prehistoric land use: Evidence from compound-specific radiocarbon analysis on Soppensee lake sediments. (15th July 2016) - Gierga, Merle; Hajdas, Irka; van Raden, Ulrike J.; Gilli, Adrian; Wacker, Lukas; Sturm, Michael; Bernasconi, Stefano M.; Smittenberg, Rienk H.
Abstract: Compound-specific radiocarbon ( 14 C) analyses allow studying the fate of individual biomarkers in ecosystems. In lakes with small catchments, terrestrial biomarkers have the potential to be used for the dating of sediments that lack the traditionally targeted terrestrial macrofossils, if the specific organic compounds are deposited soon after production. On the other hand, if the biomarkers have been stored for a significant amount of time in the soils of the catchment before transported to the lake, their age can be used to reconstruct changes in average residence time of organic material on land through time. Here we present a study based on compound-specific 14 C analysis of the sedimentary record of Lake Soppensee, Switzerland, targeting long-chain n -alkanes of exclusive terrigenous origin, and comparing them with sediment ages obtained by high-resolution macrofossil dating. Additionally, we measured 14 C ages of bulk organic matter and carbonate samples to assess the hard water effect. Prior to 3100 cal BP n -alkanes had about the same age as the sediment or they were slightly older, indicating that the vast majority of the terrestrial organic carbon transported to the lake had a short residence time on land. In the samples younger than 3100 cal BP an increasing offset is observed, indicating liberation of old buried soil organic matter that must have accumulated over the previous millennia. Our results indicate that as long as stable ecosystem conditions have prevailed, the distribution and isotopic composition of the n -alkanes can be used as environmental proxies in small catchments with limited surface runoff, confirming a few earlier studies. Highlights: Compound-specific radiocarbon analysis on long chain n -alkanes from lacustrine sediments covering the last 14, 000 years. Early prehistoric land use led to a re-mobilization of pre-aged soil organic carbon. Compound-specific 14 C analysis on terrestrial biomarker as an alternative for dating lake sediments with small catchments.